Protecting biodiversity : national laws regulating access to genetic resources in the Americas - Bass, Susan Perkoff; Ruiz Muller, Manuel (International Development Research Centre, 2000)
'Protecting Biodiversity' addresses one of the most fundamental aspects of this important issue : the lack of adequate national laws regulating access to, and compensation for, the use of local genetic resources. This book is the first to compare such laws and policies across a range of countries in both the industrialized and developing worlds, including Argentina, Canada, Colombia, Costa Rica, Paraguay, Peru, and the United States. It also presents legal viewpoints, conclusions, and solid recommendations for future action. 'Protecting Biodiversity' is the newest reference book in the rapidly emerging legal field that combines environmental, intellectual property, contract, and administrative law.